Herança da precocidade e de caracteres agronômicos em soja e seleção de linhagens com base em índices de seleção - Teixeira, Fernanda Gabriela (2017)
Breeding programs have sought the earlier cultivars development, which allow the rotation of crops and present less pressure on biotic and abiotic factors. Therefore, the inheritance for soybean cycle study contributes in providing estimates of genetic parameters, which are essential for the methods choice used in the initial and advanced stages of selection. The decision about the method adopted is important, because the selection for only one trait can cause a series of unfavorable changes in other traits. Alternatively, the selection indexes associate the information of several traits and allow to make an efficient simultaneous selection between them. In this context, this dissertation is subdivided into literature review about soybean crop and breeding, genetic parameters and selection index and two chapters. In the first chapter, a research was carried out to determine the inheritance on traits related to precocity and agronomic characters in a soybean segregating population, coming from contrasting parents to the cycle. In a greenhouse, located at UFU’s Capim Branco farm, where the P1, P2, F1 and F2 generations were evaluated from the two-parent crosses between cultivars UFUS 6901 and MG/BR46 Conquista. Heritability ranged from 2.36% for number of grains per pod to 85.39% for number of days to maturity, and the number of genes controlling those traits was 160 and two, respectively. In F2 population, there were transgressive segregants for all traits, except number of days to maturity, number of nodes and height of the first pod insertion. The genetic variance and the heritability of the agronomic traits for the F2 population coming from the hybridization of MG/BR 46 Conquista and UFUS 6901 allows the selection of superior individuals for the cycle and other traits to be obtained. The Second chapter contains a study whose objectives were to estimate genetic parameters for agronomic traits and to perform soybean strains selection using selection indexes. On field conditions, at the experimental station of Capim Branco farm, Federal University of Uberlândia (UFU), a total of 37 soybean genotypes were used in a randomized block design with three replicates, in which the agronomic traits, yield and grains were determined. It was tested twelve genotypes with a total cycle of up to 110 days and that were in the same groups of cultivars MSOY 6101 and UFUS 7910. Three lines, UFUS FG 03, UFUS FG 20 and UFUS FG 31, stood out for grain yield with values higher than the national average of 3072 kg ha-1. The right selection enabled the highest traits individual gains. The base index of Williams (1962) and the classic index proposed by Smith (1936) and Hazel (1943) presented the highest selection gain for grain yield. The genotype-ideotype distance index and the ranks sum index of Mulamba & Mock (1978) presented higher values of total selection gain. The lines UFUS FG 12, UFUS FG 14, UFUS FG 18, UFUS FG 25 and UFUS FG 31 stood out as superior genotypes in all methods of direct selection and selection indexes.